Analisis Laporan Keuangan Berdasarkan Metode Vertikal Horizontal Untuk Menilai Kinerja Keuangan Pemerintah Daerah Pada Pemerintah Kabupaten Sikka Tahun Anggaran 2019-2020 : (Studi Kasus Pada Kantor BPKAD Kabupaten Sikka) - Fransiskus Antonius (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to assess the financial performance of regional government at the Sikka Regency BPKAD office by analyzing financial reports based on vertical and horizontal methods. This was motivated by the instability of financial reports at the BPKAD office. This research uses a quantitative approach. The data collection techniques used in this research are observation and documentation. The data used is in the form of financial reports from the BPKAD office, namely balance sheets, budget realization reports, operational reports, reports on changes in excess budget balances, reports on changes in equity, and cash flows. The data analysis technique used in this research is a simple financial report calculation analysis. The research results show that vertical analysis of these reports shows improvements and changes in the financial and operational performance of regional governments from 2019 to 2020, while the results of horizontal analysis of regional government financial reports show significant changes in several aspects, including income, spending, transfers and financing from 2019 to 2020. Financial performance from 2019-2020 experienced instability or what is usually called fluctuation due to Covid-19 that hit.